(untitled) (Ágora UNLaR, 2019)
En el mundo globalizado, la creciente necesidad de interpretar productos transmediales choca con la relación asimétrica y asincrónica entre la literatura y el teatro, por un lado, y el cine, por el otro. En este trabajo tomamos la obra narrativa de Ernest Hemingway y sus adaptaciones hollywoodenses como caso testigo de algunos aspectos a considerar en las problemáticas comparaciones de este tipo. HEMINGWAY’S KILLERS: THE PROBLEM OF HOLLYWOOD’S ADAPTATIONS OF ERNEST HEMINGWAY’S FICTION Abstract In the global world, the growing need to understand transmedial works collides with the asymmetrical and asynchronous relation between literature and drama, on the one hand, and film, on the other. In this paper we take Ernest Hemingway’s fiction and its Hollywood adaptations as a leading case of some aspects to be considered in troublesome comparisons of this type. Key words: Ernest Hemingway; film adaptation; transmedia